LRRC8A is essential for swelling‐activated chloride current and for regulatory volume decrease in astrocytes. Issue 1 (29th June 2018) - Formaggio, Francesco; Saracino, Emanuela; Mola, Maria Grazia; Rao, Shreyas Balachandra; Amiry-Moghaddam, Mahmood; Muccini, Michele; Zamboni, Roberto; Nicchia, Grazia Paola; Caprini, Marco; Benfenati, Valentina
ABSTRACT: Consolidated evidence indicates that astroglial cells are critical in the homeostatic regulation of cellular volume by means of ion channels and aquaporin‐4. Volume‐regulated anion channel (VRAC) is the chloride channel that is activated upon cell swelling and critically contributes to cell volume regulation in astrocytes. The molecular identity of VRAC has been recently defined, revealing that it belongs to the leucine‐rich repeat‐containing 8 (LRRC8) protein family. However, there is a lack of evidence demonstrating that LRRC8A underpins VRAC currents in astrocyte. Nonetheless, direct evidence of the role of LRRC8A in astrocytic regulatory volume decrease remains to be proved. Here, we aim to bridge this gap in knowledge by combining RNA interference specific for LRRC8A with patch‐clamp analyses and a water‐permeability assay. We demonstrated that LRRC8A molecular expression is essential for swelling‐activated chloride current via VRAC in primary‐cultured cortical astrocytes. The knockdown of LRRC8A with a specific short interference RNA abolished the recovery of the cell volume after swelling induced by hypotonic challenge. In addition, immunoblotting, immunofluorescence, confocal imaging, and immunogold electron microscopy demonstrated that LRRC8A is expressed in the plasma membrane of primary cortical astrocytes and in situ in astrocytes at the perivascular interface with endothelial cells. Collectively, our results suggest that LRRC8A is an essential subunit of VRAC and a key factor for astroglial volume homeostasis.—Formaggio, F., Saracino, E., Mola, M. G., Rao, S. B., Amiry‐Moghaddam, M., Muccini, M., Zamboni, R., Nicchia, G. P., Caprini, M., Benfenati, V. LRRC8A is essential for swelling‐activated chloride current and for regulatory volume decrease in astrocytes. FASEB J. 33, 101–113 (2019). www.fasebj.org